2020
DOI: 10.1177/0019793920927693
|View full text |Cite
|
Sign up to set email alerts
|

Editorial Essay: Introduction to a Special Issue on Improving Private Regulation of Labor in Global Supply Chains: Theory and Evidence

Abstract: A s we write this introductory essay on private regulation in global supply chains, we are in the midst of a pandemic caused by COVID-19. Beyond the health care crisis, the economic disruption is devastating. Millions of workers in global supply chains are losing their jobs as companies cut production in response to declining demand. This trend is especially true of the apparel supply chain, which is the key focus of the articles in this special issue. As Mark Anner's timely survey in March 2020 suggests, more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 22 publications
0
14
0
1
Order By: Relevance
“…As for the role of institutional-field and societal-level dynamics, studies of the limitations of corporate global regulation implemented through private labour governance are also instructive (Amengual and Kuruvilla 2020;Short, Toffel and Hugill 2020). These studies suggest that the extent to which labour standards can protect workers and their rights -for instance through a reduction or suppression of local decoupling (Bartley and Egels-Zandén 2015) -depends not only on organizational factors but also the institutional context within which factories operate (Short, Toffel and Hugill 2020).…”
Section: Research Direction #3: Harnessing the Regulatory Potential O...mentioning
confidence: 99%
See 1 more Smart Citation
“…As for the role of institutional-field and societal-level dynamics, studies of the limitations of corporate global regulation implemented through private labour governance are also instructive (Amengual and Kuruvilla 2020;Short, Toffel and Hugill 2020). These studies suggest that the extent to which labour standards can protect workers and their rights -for instance through a reduction or suppression of local decoupling (Bartley and Egels-Zandén 2015) -depends not only on organizational factors but also the institutional context within which factories operate (Short, Toffel and Hugill 2020).…”
Section: Research Direction #3: Harnessing the Regulatory Potential O...mentioning
confidence: 99%
“…These studies suggest that the extent to which labour standards can protect workers and their rights -for instance through a reduction or suppression of local decoupling (Bartley and Egels-Zandén 2015) -depends not only on organizational factors but also the institutional context within which factories operate (Short, Toffel and Hugill 2020). In particular, the existence of public governance processes can play a central role in the effective regulation of local labour rights (Amengual and Kuruvilla, 2020;Stroehle 2017). Such insights suggest that future studies should consider not only the role of private standards and governance but also that of governments, in particular local public authorities, in making CSR/SD boundary processes more inclusive.…”
Section: Research Direction #3: Harnessing the Regulatory Potential O...mentioning
confidence: 99%
“…According to more recent studies, analyses that have focused on regulatory design underemphasize the role of the State and other contextual elements in successful regulation (Huq 2020;Bartley 2018;Tanjeem 2017). They have pointed to instances in which workers' organizations and state institutions can either assist or weaken regulatory institutions (Fine 2017;Locke 2013;Piore and Schrank 2008;McCallum 2013;Anner, Bair and Blasi 2013;Amengual 2014;Amengual and Kuruvilla 2020;Toffel, Short and Ouellet 2015;Seidman 2007 andBair, Anner and Blasi 2020). At the micro level, case studies have demonstrated that interactions among the government labour inspectorate, private compliance initiatives and trade unions affect outcomes in terms of compliance with labour law.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Given the Accord's drawn-out demise, an examination of why it was so controversial is crucial to understanding the sustainability of regulatory institutions governing global supply chains (Bair, Anner and Blasi 2020;Amengual and Kuruvilla 2020). What were the contextual determinants of this outcome?…”
Section: Introductionmentioning
confidence: 99%
“…Dada la prolongada agonía que llevó a la terminación del Acuerdo, examinar por qué fue tan controvertido resulta crucial para entender la sostenibilidad de las instituciones reguladoras de las cadenas mundiales de suministro (Bair, Anner y Blasi 2020;Amengual y Kuruvilla 2020). ¿Cuáles fueron los determinantes contextuales que condujeron a ese desenlace?…”
Section: Introductionunclassified